Hepatitis E Virus: Comprehensive Virological Insights, Diagnostic Strategies, and Laboratory Management for Clinical and Research Specialists - Bajunaid , Huda Ahmad A; Tukruna, Neamat Bakr Ali; Alabdulsalam, Hind Saad Mohammed; Hayan, Rashad Mohammad; Alhadri, Ateyah Laheg Nami; Alsaiari, Fatimah Sared; Zalah, Ahmed Abdu Ahmed; Alebaidi, Saleh Ahmad S; Alblowi, Mohammad Zaher; Jafar, Mahhani Hamad; Almadkhly, Hadeel Hassan; Abdulwahed, Walaa; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Hepatitis E virus (HEV) is a major global cause of acute viral hepatitis, with significant morbidity and mortality in high-risk populations. It is a non-enveloped, single-stranded RNA virus transmitted primarily via the fecal-oral route, though zoonotic transmission is increasingly recognized. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review provides a comprehensive update on HEV for clinical and research specialists, covering its virology, diagnostic strategies, and laboratory management to improve detection and patient care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The synthesis is based on a detailed analysis of HEV's virological characteristics, including its genotypes and their distinct epidemiological patterns. Diagnostic approaches are evaluated, comparing serological assays (anti-HEV IgM/IgG) and molecular methods (PCR for HEV RNA) for acute and chronic infection. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> HEV genotypes 1 and 2 cause waterborne outbreaks in developing regions, while genotypes 3 and 4 are zoonotic and responsible for sporadic cases in developed countries. Infection is often self-limiting but can lead to fulminant hepatitis in pregnant women and chronic infection in immunocompromised individuals. Diagnosis relies on a combination of serology and PCR, with the latter being essential for confirming chronic infection in immunosuppressed patients where antibody responses may be blunted. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> HEV is a complex pathogen with a variable clinical presentation. Accurate diagnosis requires an understanding of its virology and the strategic use of laboratory tests. Enhanced surveillance, targeted testing in high-risk groups, and a multidisciplinary approach are crucial for effective management and prevention.